1996
DOI: 10.1056/nejm199610243351706
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Academic Advancement — Results of a National Study of Pediatricians

Abstract: Lower rates of academic productivity, more time spent in teaching and patient care and less time spent in research, less institutional support for research, and lower rates of specialization in highly paid subspecialties contributed to the lower ranks and salaries of female faculty members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
1
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(170 citation statements)
references
References 29 publications
5
158
1
6
Order By: Relevance
“…[19][20][21][22] An adequate period of time dedicated to publishing activities is an important predictive factor in scientific publishing. 17,20,22 Our study found that a higher number of respondents from France had at least 1 publication in their name, whatever the type of publication evaluated. Nevertheless, there were several differences between respondents from France and Quebec.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…[19][20][21][22] An adequate period of time dedicated to publishing activities is an important predictive factor in scientific publishing. 17,20,22 Our study found that a higher number of respondents from France had at least 1 publication in their name, whatever the type of publication evaluated. Nevertheless, there were several differences between respondents from France and Quebec.…”
Section: Discussionmentioning
confidence: 50%
“…Kaplan et al and Barnett et al showed that males publish more than females. 17,18 Having tenure, having completed a doctorate, and having completed a fellowship program are predictive of scientific publishing. [19][20][21][22] An adequate period of time dedicated to publishing activities is an important predictive factor in scientific publishing.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a scarcity of women in leadership positions in academic medicine has persisted in the US despite their increasing numbers in medical training (24) (Table 3). In 2002, 29% of the entire faculty for all basic sciences and clinical sciences were women; they represented 24% of associate professors and 13% of full professors (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Percentages of women in specific medical specialties are included in Table 3.…”
Section: North Americamentioning
confidence: 99%
“…En primer lugar y como ya se ha puesto de manifiesto en la introducción de este trabajo, la literatura existente sobre el tema resalta que la productividad en investigación de las mujeres suele ser inferior a la de los hombres (Abramo et al, 2009;Kaplan et al, 1996;Leahey, 2006;Mauleón y Bordons, 2006;Maz-Machado et al, 2011) y que éstas, debido a su reciente entrada en la universidad, necesitan algo más de tiempo para situarse entre la élite investigadora . Esto es comprensible y parece estar asumido en los autores de trabajos similares, tanto en España como en otros países, pero, según los resultados obtenidos en esta investigación, si se tienen en cuenta solo los últimos diez años, la producción investigadora de las mujeres también es menor, sobre todo en artículos publicados en revistas del JCR y en tesis doctorales dirigidas; dos de los indicadores más relevantes para medir la productividad científica de profesores e investigadores a nivel nacional e internacional.…”
Section: áRea Sexounclassified
“…La edad también es una variable relevante, pues hay autores que defienden que durante ciertos periodos de la vida de las mujeres se observa un descenso en la producción, sobre todo a partir de los 40 años (Lariviere et al, 2011;Mauleón y Bordons, 2006). Una visión llamativa, de alto contenido social, es la que aportan Kaplan et al (1996), quienes concluyen que las mu-anales de psicología, 2012, vol. 28, nº 2 (mayo) jeres investigadoras presentan tasas más bajas de productividad científica porque dedican más tiempo y preocupación a la docencia y al cuidado de los pacientes, en las disciplinas médicas, con lo que poseen menos tiempo para dedicar a la investigación.…”
Section: Introductionunclassified